Pembelajaran Memorisasi Dalam Ulangan 6:6-9 - I Putu Ayub Darmawan (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2019)
The Bible in Deuteronomy 6: 6-9 gives orders to carry out children's education. The text of Deuteronomy 6: 6-9 is generally understood to be limited to the mandate of education in the family, but the author views if the text of Deuteronomy 6: 6-9 also shows a learning model. For this reason, the author analyzes the text of Deuteronomy 6: 6-9. The analysis of the text appears if there is a memorization learning process. The memorization learning process is carried out by delivering teaching repeatedly and accompanied by media available in the family environment. This learning theoretically helps to improve understanding because there is a process of recording, storing, and calling that is more effective and allows deepening of the meaning of information.AbstrakAlkitab dalam Ulangan 6:6-9 memberikan perintah untuk melaksanakan pendidikan anak. Teks Ulangan 6:6-9 umumnya dipahami sebatas sebagai mandat pendidikan dalam keluarga, tetapi penulis memandang jika teks Ulangan 6:6-9 juga menunjukkan sebuah model pembelajaran. Untuk itu penulis melakukan analisis terhadap teks Ulangan 6:6-9. Dari analisis terhadap teks tersebut tampak jika terdapat proses pembelajaran memorisasi. Proses pembelajaran memorisasi dilakukan dengan menyampaikan pengajaran secara berulang dan disertai dengan media yang tersedia di lingkungan keluarga. Pembelajaran ini secara teoritis membantu untuk meningkatkan pemahaman sebab terjadi proses perekaman, penyimpanan, dan pemanggilan yang lebih efektif dan memungkinkan terjadinya pendalaman terhadap makna pada suatu informasi.